2007
DOI: 10.1016/j.biomaterials.2007.07.013
|View full text |Cite
|
Sign up to set email alerts
|

PEEK biomaterials in trauma, orthopedic, and spinal implants

Abstract: Since the 1980s, polyaryletherketones (PAEKs) have been increasingly employed as biomaterials for trauma, orthopedic, and spinal implants. We have synthesized the extensive polymer science literature as it relates to structure, mechanical properties, and chemical resistance of PAEK biomaterials. With this foundation, one can more readily appreciate why this family of polymers will be inherently strong, inert, and biocompatible. Due to its relative inertness, PEEK biomaterials are an attractive platform upon wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
1,518
3
30

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,987 publications
(1,679 citation statements)
references
References 174 publications
15
1,518
3
30
Order By: Relevance
“…Interest in improving PEEK's osseointegration has accelerated in recent years after numerous reports have described its inability in smooth form to facilitate bone apposition [9,23,25,34,51]. Reasons why this interest persists (as opposed to abandoning PEEK altogether) are often attributed to the other qualities of PEEK that make it favorable in orthopaedic and spinal applications, mainly its radiolucency, MRI compatibility, high strength, and fatigue resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interest in improving PEEK's osseointegration has accelerated in recent years after numerous reports have described its inability in smooth form to facilitate bone apposition [9,23,25,34,51]. Reasons why this interest persists (as opposed to abandoning PEEK altogether) are often attributed to the other qualities of PEEK that make it favorable in orthopaedic and spinal applications, mainly its radiolucency, MRI compatibility, high strength, and fatigue resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Polyetheretherketone (PEEK) is a polymer widely used in orthopaedic and spinal applications such as soft tissue repair and spinal fusion devices as a result of its high strength, fatigue resistance, radiolucency, and favorable biocompatibility in osseous environments [25,38,45,47,50]. However, attributable in part to PEEK's relatively inert and hydrophobic surface, recent evidence has demonstrated that smooth PEEK can exhibit poor osseointegration [9,25] and fibrous capsule formation around the implant [23,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bisphenolate salt is formed in situ from bisphenol and either added sodium or added alkali metal carbonate or hydroxide, by the Williamson ether synthesis. PEEK is a semicrystalline thermoplastic with good mechanical properties [1]. The chemical structure of polyaromatic ketones provides stability at high temperatures (exceeding 300 °C), resistance to chemical and radiation damage, compatibility with many reinforcing agents (such as glass and carbon fibers), and greater strength (on a per mass basis) than many metals, making it highly attractive in industrial applications, such as aircraft and turbine blades, for example [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical structure of polyaromatic ketones provides stability at high temperatures (exceeding 300 °C), resistance to chemical and radiation damage, compatibility with many reinforcing agents (such as glass and carbon fibers), and greater strength (on a per mass basis) than many metals, making it highly attractive in industrial applications, such as aircraft and turbine blades, for example [2,3]. PEEK is also considered an advanced biomaterial used in medical implants, often reinforced by biocompatible fibres such as carbon [1]. In dentistry, this material is mainly used as a plastic temporary abutment for implants in the fabrication of temporary crowns [4].…”
Section: Introductionmentioning
confidence: 99%